Activity of ceftolozane/tazobactam against Gram-negative isolates among different infections in Hong Kong: SMART 2017–2019. Issue 4 (22nd April 2022) - Karlowsky, James A.; Lob, Sibylle H.; Khan, Aaron; Chen, Wei-Ting; Woo, Patrick C. Y.; Seto, Wing Hong; Ip, Margaret; Leung, Stanley; Wong, Queenie W.-L.; Chau, Rene W. Y.; DeRyke, C. Andrew; Young, Katherine; et al.
Abstract : Introduction. Ceftolozane/tazobactam was approved by the Drug Office, Department of Health, Government of the Hong Kong Special Administrative Region in 2017. Hypothesis/Gap Statement. Currently the in vitro activity of ceftolozane/tazobactam against Gram-negative pathogens isolated from patients in Hong Kong is undocumented. It would be prudent to document the activity of ceftolozane/tazobactam against Pseudomonas aeruginosa and Enterobacterales isolated from hospitalized patients in Hong Kong. Aim. To describe the in vitro susceptibility of recent clinical isolates of P. aeruginosa and the two most common Enterobacterales species ( Klebsiella pneumoniae, Escherichia coli ) cultured from respiratory tract, intra-abdominal, urinary tract and bloodstream infection samples to ceftolozane/tazobactam and other commonly used antimicrobial agents. Methodology. CLSI-defined broth microdilution MICs were determined and interpreted for Gram-negative isolates collected in Hong Kong from 2017 to 2019 by the SMART surveillance programme. Results. For P. aeruginosa, 96.7 % of isolates ( n =210) were susceptible to ceftolozane/tazobactam, while susceptibility rates were ≥14 % lower to meropenem (82.9 % susceptible), cefepime (82.4 %), ceftazidime (81.4 %), piperacillin/tazobactam (76.7 %) and levofloxacin (79.5 %). Ceftolozane/tazobactam inhibited 85.7 % of piperacillin/tazobactam-nonsusceptible isolates, 80.6–82.1 % of cefepime-, ceftazidime- or meropenem-nonsusceptible isolates, and 75.9 % of multidrug-resistant (MDR) isolates of P. aeruginosa . For K. pneumoniae, 96.1 % of isolates ( n =308) were susceptible to ceftolozane/tazobactam compared with meropenem (99.0 % susceptible), piperacillin/tazobactam (93.8 %), cefepime (85.7 %) and ceftazidime (85.4 %). The majority (88.3 %) of ESBL (extended-spectrum β-lactamase) non-CRE (carbapenem-resistant Enterobacterales) phenotype isolates of K. pneumoniae were susceptible to ceftolozane/tazobactam, comparable to piperacillin/tazobactam (85.0 %) but lower than meropenem (100 %). For E. coli, 98.5 % of isolates ( n =609) were susceptible to ceftolozane/tazobactam compared to meropenem (99.3 % susceptible), piperacillin/tazobactam (96.7 %), ceftazidime (82.3 %) and cefepime (76.5 %). The majority (96.7 %) of ESBL non-CRE phenotype isolates of E. coli were susceptible to ceftolozane/tazobactam, similar to both meropenem (100 %) and piperacillin/tazobactam (94.5 %). Conclusions. Overall, >96 % of clinical isolates of P. aeruginosa, K. pneumoniae and E. coli collected in Hong Kong in 2017–2019 were susceptible to ceftolozane/tazobactam, while the activity of several commonly prescribed β-lactams was reduced, especially for P. aeruginosa . Continued surveillance of ceftolozane/tazobactam and other agents is warranted.